THE COMPARISON OF WORDS IN THE TRANSLATION IS IN THE EXAMPLE OF ENGLISH AND UZBEK - Anjela Kuganova Alimardonovna ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses about the comparative change of words in the process of translating from English to Uzbek and from Uzbek to English, and discusses some given examples.